TOWARDS THE OVERCOMING OF ISLAMISM AND POPULISM: FROM INTERNATIONAL RELATIONS TO INTERRELIGIOUS DIALOGUE - Vulić, Miloš (Political Review, 2025)
This study aims to critically examine the thesis of the “clash of civilizations” and to explore whether such a clash is inevitable when the Eastern-Muslim and Western-Christian worlds meet, as well as whether the mutual fear between them is justified and how it is generated and mobilized. In the introductory section, we will provide an overview of the historical relations between these “two worlds” to identify the factors that opened the possibility for the emergence of radical attitudes stemming from concepts such as Islamism and Populism. After that, we will address the question of which factors contributed to their sudden “revival”, with particular focus on one of the most frequently cited causes: the refugee crisis. We will examine how this crisis emerged and the nature of the reactions it provoked, specifically the politicization of otherness. In the subsequent analysis, special attention will be given to Western Populism and its Islamophobic policies. Finally, we will explore the concepts of constitutional patriotism, Euro-Islam, and human (universal) brotherhood as potential pathways toward overcoming the negative dichotomy inherent in the notions of Islam and the West, particularly in the context of the role of interreligious dialogue in international relations and its contribution to the depoliticization of otherness.
Keywords: Islam; West; Islamism; Populism; Refugee Crisis; Politicization of otherness; Constitutional Patriotism; Euro-Islam; Universal Fraternity; Depoliticization of otherness